Proper orthogonal decomposition method for some parabolic type equations - Jankevičiūtė, Gerda; Leonavičienė, Teresė; Čiegis, Raimondas (Lietuvos matematikos rinkinys, 2012)
In this paper proper orthogonal decomposition method for 1D parabolic type equations is described. First basic ideas of method are presented and application scheme for compiutations is derived. Later the sensitivity of proper orthogonal decomposition method is analyzed depending on the diffusion coefficient and source function. The obtained numerical results are presented in figures and tables.
Keywords: parabolic equations; numerical methods; proper orthogonal decomposition method